2013
DOI: 10.3343/alm.2013.33.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methylation Profiling in Cancerous and Their Corresponding Normal Tissues from Korean Patients with Breast Cancer

Abstract: BackgroundAberrant DNA hypermethylation plays a pivotal role in carcinogenesis and disease progression; therefore, accurate measurement of differential gene methylation patterns among many genes is likely to reveal biomarkers for improved risk assessment. We evaluated the gene hypermethylation profiles of primary breast tumors and their corresponding normal tissues and investigated the association between major clinicopathological features and gene hypermethylation.MethodsA single reaction using methylation-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
3
21
0
1
Order By: Relevance
“…The malfunctioning of this checkpoint might be particularly important in the initiation of the tumor. CDKN2B has been repeatedly found to be hypermethylated – a sign that the gene has been shut down, in benign lesions of the breast and in BCIS [ 30 , 31 ], indicating its involvement in the early phases of carcinogenesis. Furthermore, Worsham and colleagues found that CDKN2B was crucial for initiating immortalization events but less important for progression to malignancy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The malfunctioning of this checkpoint might be particularly important in the initiation of the tumor. CDKN2B has been repeatedly found to be hypermethylated – a sign that the gene has been shut down, in benign lesions of the breast and in BCIS [ 30 , 31 ], indicating its involvement in the early phases of carcinogenesis. Furthermore, Worsham and colleagues found that CDKN2B was crucial for initiating immortalization events but less important for progression to malignancy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three DNA methyltransferases (DNMT), namely DNMT1, DNMT3a and DNMT3b, are responsible for transcriptional silencing through the addition of methyl groups to cytosine residues preceding guanine (CpG), which, during normal development and in certain pathological conditions, occur on areas concentrated with CpGs, called 'CpG islands' just upstream of gene promoters in mammalian cells [36]. Aberrant DNA hypermethylation in the normally unmethylated promoter regions of tumor suppressive genes has been proposed as one mechanism of their suppression in cancer cells [37][38][39]. Tumor cells of various cancer types have also been found to exhibit global hypomethylation, which may correspond to a worse prognosis [40].…”
Section: Dna Methylationmentioning
confidence: 99%
“…The general characteristics of eligible studies were summarized and displayed in Table 1. A total of 2482 BC patients and 1212 controls were employed in multiple countries or regions including Asia (n=10) (Jin et al 2001;Jing et al 2010;Jung et al 2013;Lee et al 2004;Liu et al 2007;Park et al 2011b;Prasad et al 2008;Zhang et al 2007), Europe (n=13) (Fridrichova et al 2015;Hoque et al 2009;Jeronimo et al 2008;Martins et al 2011;Matuschek et al 2010;Muller et al 2003;Parrella et al 2004;Rykova et al 2004;Van der Auwera et al 2009a;Van der Auwera et al 2009b;Van der Auwera et al 2008;Wojdacz et al 2011b), Africa (n=2) (Hoque et al 2006;Swellam et al 2015), North America (n=9) (Brooks et al 2010;Chen et al 2011;Cho et al 2010;Dulaimi et al 2004;Lewis et al 2005;Shinozaki et al 2005;Taback et al 2006;Virmani et al 2001) and Oceania (n=1) (Pang et al 2014). Furthermore, the methylated APC levels in BC patients and controls were examined with 6 methods.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%